THE CONTRIBUTION OF PANCASARI TOURISM VILLAGE TO SUSTAINABLE RURAL ECONOMIC DEVELOPMENT - Ni Kadek Sinarwati; Nyoman Trisna Herawati; I Gede Putu Banu Astawa; I Komang Trisna Eka Putra; Ngurah Eka Utama Putra (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2026)
PURPOSE - This study examines the contribution of tourism villages to achieving sustainable rural economic development, the strategies used to strengthen this contribution, the challenges encountered, and the roles of stakeholders in supporting sustainable outcomes.METHODOLOGY - A descriptive qualitative approach was applied in Pancasari Tourism Village, Sukasada Subdistrict, Buleleng Regency. The village was selected for three reasons. First, Pancasari is officially designated as a tourism village under the Buleleng Regent’s Decree No. 430/239/HK/2022. Second, Sukasada Subdistrict recorded the lowest Village Development Index (IDM) in Buleleng Regency based on 2023 data from the Ministry of Villages and Rural Development. Third, among ten tourism villages in Sukasada Subdistrict, Pancasari has the highest IDM score and the largest number of tourist attractions. Participants included village government officials, such as the village head, village secretary, directors of village-owned enterprises, and community representatives managing tourism sites. Data were collected through interviews and documentation.FINDING - The findings indicate that Pancasari Tourism Village achieved a contribution score of 0.32 toward sustainable rural economic development, categorized as low. Improvement efforts include organizing poverty assistance data, facilitating microenterprise access to capital through Bank Rakyat Indonesia, and encouraging women’s participation. Key stakeholders include village governments, local communities, and village-based financial institutions supporting local development